Kegiatan Pengabdian Masyarakat Dengan Penilaian Rasio Apolipoprotein A Dan B Dalam Memantau Risiko Penyakit Jantung Pada Lansia - Welly Hartono Ruslim; Raden Seliwat Agung Aditya; Chandy Linardi Putra (Pusat Riset dan Inovasi Nasional, 2024)
Coronary heart disease is a serious medical condition characterized by narrowing or blockage of the coronary arteries, leading to decreased blood flow to the heart and a high risk of causing chest pain, shortness of breath, fatigue and heart attack. In the elderly, coronary heart disease can worsen the quality of life and increase morbidity and mortality rates. The importance of health education and screening for apolipoprotein A (ApoA) and B (ApoB) in the elderly is crucial because the ApoA/ApoB ratio is an important indicator in monitoring the risk of heart disease. This community service activity aims to screen the ApoA/ApoB ratio as an indicator in monitoring the risk of heart disease in the elderly. With the PDCA (Plan-Do-Check-Act) approach, outreach, blood sampling, health education and evaluation of results are carried out to provide specific health recommendations. Screening results showed variations in the distribution of the ApoA/ApoB ratio between genders, emphasizing the importance of routine monitoring and healthy lifestyle interventions to prevent heart disease and improve the quality of life of the elderly.